Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1002/bit.26052
|View full text |Cite
|
Sign up to set email alerts
|

Comparative thermal inactivation analysis of Aspergillus oryzae and Thiellavia terrestris cutinase: Role of glycosylation

Abstract: Cutinase thermostability is important so that the enzymes can function above the glass transition of what are often rigid polymer substrates. A detailed thermal inactivation analysis was performed for two well-characterized cutinases, Aspergillus oryzae Cutinase (AoC) and Thiellavia terrestris Cutinase (TtC). Both AoC and TtC are prone to thermal aggregation upon unfolding at high temperature, which was found to be a major reason for irreversible loss of enzyme activity. Our study demonstrates that glycosylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 77 publications
0
33
1
Order By: Relevance
“…In contrast, expression in P. pastoris may lead to glycosylation which can have positive effects such as increased stability, as previously shown for a Thermobifida xylanase (Zhao et al, 2015), human aquaporin 10 (Öberg et al, 2011) and Rhizopus chinensis lipase (Yang et al, 2015). Shirke et al also recently reported that glycosylation stabilizes a P. pastoris -expressed cutinase from Thiellavia terrestris by inhibiting its thermal aggregation (Shirke et al, 2017). On the other hand, glycosylation may also have negative effects, as shown for example for a lipase from Rhizomucor miehei which had decreased activity upon N-glycosylation (Liu et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, expression in P. pastoris may lead to glycosylation which can have positive effects such as increased stability, as previously shown for a Thermobifida xylanase (Zhao et al, 2015), human aquaporin 10 (Öberg et al, 2011) and Rhizopus chinensis lipase (Yang et al, 2015). Shirke et al also recently reported that glycosylation stabilizes a P. pastoris -expressed cutinase from Thiellavia terrestris by inhibiting its thermal aggregation (Shirke et al, 2017). On the other hand, glycosylation may also have negative effects, as shown for example for a lipase from Rhizomucor miehei which had decreased activity upon N-glycosylation (Liu et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Such inter conversion of helices to turns are possibly due to insertion of polysaccharide into helix [14]. The changes in the secondary structure might horseradish peroxidase with starch [17], sodium carboxymethyl cellulose, methyl cellulose, and sodium carboxymethyl chitosan with β-D-glucuronidase [15] and alcohol dehydrogenase with gum Arabic complex [14], and Aspergillus oryzae cutinase with trehalose [11].…”
Section: Screening Of Polysaccharides For Non-covalent Interaction Wimentioning
confidence: 98%
“…Both the effects plays a crucial role in stabilizing the enzyme molecule by maintaining its native structural integrity at adverse conditions and also inhibits enzyme aggregation [14][15]17]. The enhanced thermostability for wild type Aspergillus oryzae cutinase (wt-AoC) [11], and Fusarium solani cutinase [6] is primarily due to excluded volume effects of trehalose.…”
Section: Thermal Inactivation Kinetics Of Cutinase In Free and Pectinmentioning
confidence: 99%
See 2 more Smart Citations